2004
DOI: 10.1002/jgm.604
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro vascular cell transfection with non‐viral vectors for in vivo applications

Abstract: FuGene 6 is an efficient non-viral transfection reagent for gene transfer in somatic smooth muscle cells in vitro and ZnCl2 enhances its efficiency. This increased expression of the transgene product is maintained after seeding in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…We have previously shown that SkM based delivery of VEGF and angiopoietin-1 transgenes to infarcted heart, either alone or in combination, gave improved neovascularization [33]. Drifting away from the use of viral vectors to alleviate safety and immunological concerns; we have optimized conditions for gene modulation of cells using cationic lipids in the presence of ZnCl 2 [14]. Our optimized procedure significantly enhanced the efficiency of hSDF-1α transfection into otherwise transfection resistant cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that SkM based delivery of VEGF and angiopoietin-1 transgenes to infarcted heart, either alone or in combination, gave improved neovascularization [33]. Drifting away from the use of viral vectors to alleviate safety and immunological concerns; we have optimized conditions for gene modulation of cells using cationic lipids in the presence of ZnCl 2 [14]. Our optimized procedure significantly enhanced the efficiency of hSDF-1α transfection into otherwise transfection resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…For these vectors, transfection conditions were optimized at various DNA:vector ratios, in the presence of 0-100μM ZnCl 2 (Merck, Germany) at 37 °C or room temperature. Cell viability was assessed with a modified MTT reduction test [14]. As maximum transfection efficiency with highest cell viability was achieved using FuGene™6/phSDF-1α (v/w) 3:2 ratio in basal DMEM containing 125μM ZnCl 2 (for 4h at 37 °C), these transfection conditions were used throughout the study.…”
Section: Transfection Of Skmmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts at this have been made with little success, because although the cells can be transfected and express after delivery in vivo, they do not necessarily engraft into the smooth muscle layer to any great extent. In one study, transfected SMCs were injected intravenously, intraperitoneally, or intramuscularly (34). Although cells injected by all routes expressed for 4 -7 days, there were no data to show where these cells actually localized because the gene expressed encoded for a secreted protein.…”
Section: Smooth Musclementioning
confidence: 99%
“…Importantly, the transfection reagent should not be allowed to attach to the used plastic ware and transfection complexes should be added to the cells in a strict dropwise manner. Fugene6 has been used efficiently in many gene therapeutic contexts (Arnold et al, 2006, Elmadbouh et al, 2004, Young et al, 2002 and has been proposed for generation of induced pluripotent stem cells (Aasen & Belmonte, 2010). It has been used successfully by us and others for keratinocyte transfection (Aasen & Belmonte, 2010, Distler et al, 2005, Radtke et al, 2009).…”
Section: Gene Therapeutic Approachesmentioning
confidence: 99%